(3VeGfGJ GdeJge ai eQMdI GdeMGceI ai GdJTQjYGJ GdNdjLjI (B/ s - (3Ydi aVd GdHhYjfjfs; (3GMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3GdeMGceI GdYGOdI gi GdeMGceI GdJi JSJhLH ebGVGI GdeJge HTCf GdGJgGe GdehLg Gdjg GeGe eMceI eSJbdI eMGjOI efTCI HMce GdbGfhf bHd GJgGeg WHbG dGLQGAGJ YdfjI jJGM dg ef NdGdgG GdOaGY Yf faSg eY GMGWJg HGdJgeI GdefShHI Gdjg hGOdI GdGJgGe GdeJhaQI VOg ceG jfHZi Gf JQGYi ajgG eHGOiA GdYdGfjI hGdTahjI hJOhjf GdGLQGAGJ hcPdc eHOC GdehGLgI Hjf GdNUhe heHOC GdeSGhGI Hjfge GeGe GdbVGAs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2006s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B806-833s
Keywords: (3GdbGfhf GdLfGFjs; (3GdeMGceI GdYGOdIs; (3SQYI GdaUd ai GdOYGhis; (3eHOC GdeSGhGI Hjf GdNUhe GeGe GdbVGAs; (3MQjI GdbGVj aj Jchjf YbjOJgs; (3JSHjH GdGMcGes; (3GdGYJQGas; (3GdWYf aj GdGMcGes; (3GdHWdGfs; (3bQjfI GdHQGAIs; (3Mb GdOaGY s; (3GSJbdGd GdbVGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs